Burnout as Moderation and Emotional Intelligence as Mediation in professional skills, Personality Characteristics, Psychological Well-Being to Individual Performance - Khoirun Nisa; Wahyu Eko Pujianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to test and analyze the influence of professional skills, personality characteristics, and psychological well-being through emotional intelligence on individual performance moderated by burnout in CV . Kozihome. This research uses a quantitative descriptive approach. This research is quantitative. The sampling technique used proportional stratified Random Sampling with a sample size of 96 employees. The statistical analysis used in this research is Partial Least Squares 4.0 (PLS). The results of this research show that: (1) there is a positive but not significant influence of professional skills on emotional intelligence, (2) there is a positive but not significant influence of personality characteristics on emotional intelligence (3) there is a significant positive influence of psychological well-being on emotional intelligence, (4) there is a negative and insignificant influence of professional skills on emotional intelligence which is moderated by burnout (5) there is a negative and insignificant influence of personality characteristics on emotional intelligence which is moderated by burnout (6) there is a negative and insignificant influence of psychological well-being on emotional intelligence which is moderated by burnout and (7) there is a positive and significant influence of emotional intelligence on individual performance.